480 Surgery for rectosigmoid peritonectomy in advanced ovarian cancer: surgical technique of visceral segmental serosectomy and 8-year experience. (13th November 2020) - Park, SJ; Kim, HS; Kim, JW
Abstract : Introduction: Tumors infiltrating rectosigmoid colon is commonly found during cytoreduction in ovarian cancer. Low anterior resection (LAR) or visceral serosal segmentectomy (VSS) can be performed for removing tumors on the rectosigmoid colon. LAR is associated with decreased bowel function, and conservatively ablating tumors on rectosigmoid colon by VSS might be safe without compromising the quality of life. Methods: From Jan 2013 to June 2020, we performed 83 cases of stage IIB to IVB ovarian cancer surgery with resection of tumors involving the rectosigmoid colon. Also, VSS was considered when the length of the tumor extent of the rectosigmoid colon was less than 18 cm, and there was no evidence of mucosal invasion, and in the other cases, LAR was performed. Results: First, the rectosigmoid colon is mobilized, and then, mesorectal excision was done, and VSS can be performed. Exposure of the muscle layer or mucosal layer can be repaired. After that, tagging suture is done at the edge, and the resected serosa area is folded and form a bowel loop. A bubble leak test was performed after the serosal repair is completed. Among 83 patients, there were no differences in clinicopathologic characteristics between LAR (n=39) and VSS (n=44) group. In terms of surgical extent, LAR showed more combined procedures related to bowel surgery. Also, there were no differences in survival, recurrence pattern, and surgical complications. Conclusions: Visceral Segmental Serosectomy is feasible and can be safely performed without significant complications and comparable survival outcomes.